Embedding‐theory‐based simulations using experimental electron densities for the environment. Issue 5 (20th July 2020) - Ricardi, Niccolò; Ernst, Michelle; Macchi, Piero; Wesolowski, Tomasz Adam
Abstract : For the first time, the use of experimentally derived molecular electron densities as ρ B (r ) in calculations based on frozen‐density embedding theory (FDET) of environment‐induced shifts of electronic excitations for chromophores in clusters is demonstrated. ρ B (r ) was derived from X‐ray restrained molecular wavefunctions of glycylglycine to obtain environment densities for simulating electronic excitations in clusters. Abstract : The basic idea of frozen‐density embedding theory (FDET) is the constrained minimization of the Hohenberg–Kohn density functional E HK [ρ] performed using the auxiliary functional, where Ψ A is the embedded N A ‐electron wavefunction and ρ B (r ) is a non‐negative function in real space integrating to a given number of electrons N B . This choice of independent variables in the total energy functional makes it possible to treat the corresponding two components of the total density using different methods in multi‐level simulations. The application of FDET using ρ B (r ) reconstructed from X‐ray diffraction data for a molecular crystal is demonstrated for the first time. For eight hydrogen‐bonded clusters involving a chromophore (represented as Ψ A ) and the glycylglycine molecule [represented as ρ B (r )], FDET is used to derive excitation energies. It is shown that experimental densities are suitable for use as ρ B (r ) in FDET‐based simulations.